Race-related host and microbe transcriptomic signatures in triple-negative breast cancer - Roshan Kumar; Susan Duyar-Ayerdi; Aishwarya Sundaresan; Vinodh Srinivasasainagendra; Chandra Sekhar Pedamallu; Michael Behring; Darshan Shimoga Chandrashekar; Isam-Eldin Eltoum; Sooryanarayana Varambally; Hemant K. Tiwari; Sadeep Shrestha; Paul L. Auer; et al. (npj Breast Cancer)
Abstract Triple-negative breast cancer (TNBC) shows racial disparities, with higher incidence in women of African ancestry (AA) compared to European ancestry (EA). Meta-transcriptomic analysis of TNBC tumor tissues from AA (n = 17) and EA (n = 19) subjects revealed distinct microbial landscapes. Hierarchical clustering based on microbial transcripts separated samples into two groups predominantly defined by racial ancestry. Bacterial genera including Hafnia and Cedecea were more abundant in AA tumors, while Erwinia was higher in EA tumors. Cellular composition analysis by xCell revealed differences in immune cell populations, with AA tumors having higher Th1 cell abundance and EA tumors containing higher macrophage M2 cell abundance. Nonetheless, AA women with high M2 abundance experienced poorer disease-free survival (DFS) than EA women. Integrative analyses revealed that high expression of human SPDYE2B gene was associated with Hafnia abundance and decreased DFS, highlighting complex host-microbe interactions in TNBC patients.